Correlation of Multiple Choice Examination Scores with Oral Examination Scores of the Second Year Undergraduate Program Faculty of Medicine Universitas Padjadjaran in Academic Year 2019/2020 - Chyntia Tika Maharani; Putri Halleyana Adrikni Rahman; Resti Gradia Dwiwina (Rifa'Institute, 2022)
Background: COVID-19 pandemic causes several changes in daily activities, one of them is medical students’ online lectures and examinations. Educational evaluation of college students from the Medical Undergraduate Study Program, Faculty of Medicine, Universitas Padjadjaran in each lesson, is done by two kinds of assessments, such as multiple choices written online examination and oral online examination. Each of them has its own advantages and disadvantages. Evaluation in Problem Based Learning (PBL) educational system is important to push the medical student’s ability in learning, evaluate the effectiveness of learning and test student’s ability in their medical knowledge. Aim: To determine the correlation between multiple-choice examination scores with oral examination scores of Second Year Undergraduate Program in Faculty of Medicine Universitas Padjadjaran Academic Year 2019/2020. Method: This research is a quantitative analytic study using a cross-sectional design. The test used is the Spearman correlation statistical test to determine the correlation between multiple-choice examination and oral examination. Result: The results of the Spearman correlation test found a correlation coefficient value of 0.307 and a p-value of 0.000 which indicates that there is a significant relationship. Conclusion: There is a weak correlation of multiple-choice examination scores with oral examination scores of Second Year Undergraduate Program in Faculty of Medicine Universitas Padjadjaran Academic Year 2019/2020